TECHNICAL AND VOCATIONAL EDUCATION: IMPERATIVES FOR SOCIO-ECONOMIC AND POLITICAL STABILITY IN NIGERIA - Ojimba, Daso Peter (European Scientific Journal, ESJ, 2013)
This paper focused on technical and vocational education as imperatives for socio-economic and political stability in Nigeria. It reviewed the concept of technical education and vocational education. Historical attempt at vocational and technical education were delved into; especially as it concerned the pre-independence and post independence era. This paper saw the education, our colonial masters bequeathed to us as â€˜generalâ€™ rather than â€œvocational/technicalâ€. However, imperatives such as vocational and technical education were critically analysed for socio-economic and political stability of Nigeria. The paper eloquently ex-rayed basic drawbacks of vocational and technical education in Nigeria to include: lack of funds, poor facilities, brain drain syndrome, staff retention problem, curriculum, inadequacy, apathy of political office holders/lawmakers. Furthermore, the way forward and its attendant solutions to these problems were proffered. The paper suggested that a wholistic reform towards technical and vocational education and a deliberate attempt to lift the programme is the only panacea to a technological ender ado in Nigeria with socio-economic and political stability in its purview.